Rethinking running biomechanics: a critical review of ground reaction forces, tibial bone loading, and the role of wearable sensors - Xiang, Liangliang; Gao, Zixiang; Wang, Alan; Shim, Vickie; Fekete, Gusztáv; Gu, Yaodong; Fernandez, Justin (Frontiers in Bioengineering and Biotechnology, 2024)
This study presents a comprehensive review of the correlation between tibial acceleration (TA), ground reaction forces (GRF), and tibial bone loading, emphasizing the critical role of wearable sensor technology in accurately measuring these biomechanical forces in the context of running. This systematic review and meta-analysis searched various electronic databases (PubMed, SPORTDiscus, Scopus, IEEE Xplore and ScienceDirect) to identify relevant studies. It critically evaluates existing research on GRF and tibial acceleration (TA) as indicators of running-related injuries, revealing mixed findings. Intriguingly, recent empirical data indicate only a marginal link between GRF, TA, and tibial bone stress, thus challenging the conventional understanding in this field. The study also highlights the limitations of current biomechanical models and methodologies, proposing a paradigm shift towards more holistic and integrated approaches. The study under-scores wearable sensors' potential, enhanced by machine learning, in transforming the monitoring, prevention, and rehabilitation of running-related injuries.OR "GRF" OR "loading rate" OR "impact loading" OR "impact peak" OR "active peak" OR "braking force" OR "propulsive force") AND ("running" OR "runner*" OR "jog" OR "jogging")